Effect of work-family conflict on job satisfaction of small enterprise managers - Kwadwo Tuffour, Joseph (Economic and business review, 2022)
Balancing priorities and demands of work and family at the same time can be quite hectic and likely to generate conflicts. Workers must find strategies to manage the exigencies of modern living in order to maintain job satisfaction as well as family relationships. This study investigates the effect of work-family conflict's two directions on job satisfac- tion, and the moderating role of resilience. The study used a cross-sectional survey method to collect data from 293 small- scale enterprise managers, utilizing a structured questionnaire. Correlation and analysis of variance techniques were used. The results reveal that the work-family conflict has a significant positive effect on job satisfaction. Small enterprise leaders experience enough job satisfaction to better withstand the conflicts that arise from their work roles due to some context-specific factors. As small enterprise leaders' job role conflicts increase, there is also an increase in resilience to overcome the conflict. Also, resilience positively moderates the relationship between work-family conflict and job satisfaction. Increasing levels of entrepreneurs' work-family conflict come with increasing levels of resilience. Moreover, resilience also positively moderates the effect of family-work conflict on job satisfaction. It is recommended that or- ganisations and policy-makers should undertake resilience training to equip small enterprise leaders to cope better with stress, be more satisfied and productive.
Keywords: kadri; management; personnel; usklajevanje službenega in zasebnega življenja; work-life balance